Surgical management of atraumatic splenic rupture - Walker, Alyssa M.; Foley, Eugene F. (International Surgery Journal, 2016)
Atraumatic splenic rupture (ASR) is a rare, spontaneous, and potentially life-threatening condition that occurs in the absence of trauma; yet the management of ASR has largely defaulted to the treatment algorithm related to blunt splenic trauma. Our aim is to determine if it is appropriate and safe to use the treatment algorithm for blunt splenic trauma in the management of both pathological and non-pathological ASR. We present a case of non-pathological ASR that was successfully managed without splenectomy. A comprehensive literature review on spontaneous ASR was also performed to include publications from January 1975 to February 2015. 914 total cases of ASR were identified: 70 non-pathological and 844 pathological. Overall, 86.5% of these patients received splenectomy based on the presence or absence of traditional signs of clinical instability or deterioration, as utilized in cases of traumatic splenic rupture. There were only 11 non-pathological cases detailed. Unlike our present case, all of these cases resulted in splenectomy. The present case is that of a 37 year-old man with grade III splenic rupture, successfully managed without surgery or splenectomy. Details regarding ASR patients are limited in current literature. The majority of patients with ASR will receive splenectomy, regardless of etiology. Our review would suggest that it is appropriate and safe to pursue conservative non-surgical therapy in select patients who present with ASR of any given etiology (even non-pathological), while utilizing the same indications for splenectomy used in cases of blunt abdominal trauma.